What do children with social, emotional and behavioural difficulties think about themselves in early childhood? - Heinonen Marianna H.; Pihlaja Päivi M. E. (Routledge, Taylor and Francis Group, 2022)
The aim of this study was to discover what kind of perceptions young children in need of social, emotional, and behavioural support have about themselves. The interest was especially in social and emotional self-perceptions. For this study, ten children attending Finnish early childhood education and care were interviewed in spring 2016 and the material was analysed by using thematic analysis. Several developmental characteristics, typical for children aged 4–7 years, were found in the analysis such as general positivity of self-perceptions. However, the children’s perceptions also included atypical and negative features which manifested in various ways. Based on these features, four self-perception types were formed to describe the levels of positivity and negativity as well as the different features typical for each child and for each self-perception type. The results and possible explanations of the findings are discussed.